The effects of acute yoga practice on heart rate and heart rate variability responses to mental stress. - Chu, I.-Hua; Lin, Yuh-Jen; Wu, Wen-Lan; Yu, Tzu-Cheng; Lin, I.-Mei; Chang, Yu-Kai (International Journal of Sport & Exercise Psychology, 2023)
Yoga has been shown to reduce stress and to provide health benefits for a number of stress-related disorders. However, the effects and mechanism of an acute bout of yoga practice on relieving stress remain unclear. The aim of this study was to examine the effect of a single bout of yoga on heart rate (HR) and heart rate variability (HRV) response to and recovery from mental stress. This study was conducted with a randomised, counterbalanced, crossover design. A total of 44 participants (mean age 24.58 ± 3.84) completed two conditions (yoga and video watching (VW)) in a randomly assigned order. After each condition, participants underwent a Stroop task and mental arithmetic task. HR and HRV, measured via electrocardiogram, were recorded and analyzed at rest, during each condition, and during the stress and recovery periods. HR was significantly lower during the yoga condition as compared to that during the VW condition. There was no significant difference in HRV observed between the conditions. During both mental stress and recovery periods, there was no significant difference in HR or HRV responses between the yoga and VW conditions. These findings suggested that an acute bout of yoga practice was not superior to quiet sitting in reducing HR and HRV reactivity to and recovery from mental stress. Future studies may consider investigating individuals with exaggerated cardiovascular reactivity to further examine the potential reactivity-lowering effect of yoga.